PCR-Based Rapid Identification System Using Bridged Nucleic Acids for Detection of Clarithromycin-Resistant Mycobacterium avium-M. intracellulare Complex Isolates - Hirama, Takashi (J Clin Microbiol, 2016)
The nontuberculous mycobacteria (NTM) cause miscellaneous disorders in humans, especially in the lungs, which present with a variety of radiological features. To date, knowledge of the pathogenic role of the Mycobacterium avium-intracellulare complex (MAC) in the human lung and the definitive criteria for initiating multidrug therapy are still lacking. However, there is little doubt that clarithromycin is the most efficacious drug among the various treatment regimens for lung NTM. In this study, with the use of a bridged nucleic acid (BNA) probe a detection system based on a real-time PCR (BNA-PCR) for the identification of the point mutations at position 2058 or 2059 in domain V of the 23S rRNA gene responsible for clarithromycin resistance was developed and has been assessed using MAC isolates from clinical samples. Out of 199 respiratory specimens, the drug susceptibility test demonstrated 12 strains resistant to clarithromycin, while the BNA-PCR showed 8 strains carrying the point mutation at position 2058 or 2059 of the 23S rRNA gene. This system revealed that there were mycobacterial strains resistant to clarithromycin which do not carry previously identified resistance genes. This paper documents a novel system for detecting clarithromycin-resistant strains and demonstrates that although these mutations are tacitly assumed to account for >90% of the reported resistant mutants, there is a significant fraction of resistant mutants that do not harbor these mutations. Therefore, unknown mechanisms affecting clarithromycin resistance remain to be elucidated.